Transpedicular Screw Placement Accuracy Using the O-Arm Versus Freehand Technique at a Single Institution. Issue 3 (April 2022) - Crawford, Benjamin D.; Nchako, Corbyn M.; Rebehn, Kelsey A.; Israel, Heidi; Place, Howard M.
Study Design: Retrospective cohort. Objective: The objective of this study was to assess the effectiveness of the O-arm as an intraoperative imaging tool by comparing accuracy of pedicle screw placement to freehand technique. Methods: The study comprised a total of 1161 screws placed within the cervical (n = 187) thoracic (n = 657), or lumbar (n = 317) spinal level. A pedicle breach was determined by any measurable displacement of the screw outside of the pedicle cortex in any plane on postoperative images. Each pedicle screw was subsequently classified by its placement relative to the targeted pedicle. Statistical analysis was then performed to determine the frequency and type of pedicle screw mispositioning that occurred using the O-arm versus freehand technique. Results: A total of 155 cases (O-arm 84, freehand 71) involved the placement of 454 pedicle screws in the O-arm group and 707 pedicle screws in the freehand group. A pedicle breach occurred in 89 (12.6%) screws in the freehand group and 55 (12.1%) in the O-arm group ( P = .811). Spinal level operated upon did not influence pedicle screw accuracy between groups ( P > .05). Three screws required revision surgery between the 2 groups (O-arm 1, freehand 2, P > .05). The most frequent breach type was a lateral pedicle breach (O-arm 22/454, 4.8%; freehand 54/707, 7.6%), without a significant difference between groups ( P > .05). Conclusions: The use of the O-arm coupled with navigation does not assure improved transpedicular screw placement accuracy when compared with the freehand technique.